Linguistic Identity Transformation: An Empirical Study of Javanese Language Shift toward Indonesian - Ayang Winda; Nurfithri; Rahma Sakina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
in recent years, there has been a significant decline in the use of the Javanese language, particularly among younger generations living in urban areas. This phenomenon is influenced by various factors, such as the dominance of the Indonesian language in the education system and media, the impact of social environments, and the decreasing role of families in transmitting local languages. This study aims to examine the language shift from Javanese to Indonesian and its impact on the linguistic identity of young people. A descriptive qualitative approach was employed, involving ten participants aged 20–25 years residing in Central Java and the Special Region of Yogyakarta. Data were collected through in-depth interviews and documentation, then analyzed thematically to identify patterns of language use and shifts in linguistic identity. The findings indicate that most participants prefer using Indonesian because it is perceived as more practical, modern, and suitable for cross-cultural communication. Javanese is still used, but it is limited to specific contexts, such as interactions with parents or traditional events. Nevertheless, participants continue to show emotional attachment to their Javanese identity. Their linguistic identity is flexible and constantly negotiated depending on the social context. This study concludes that language shift is a complex phenomenon that involves not only linguistic aspects but also reflects changing values, attitudes, and identities within society.